On Morrey-type classes of harmonic functions - Zeren, Yusuf; Abdullayeva, Rubaba H.; Cetin, Seyma (SPRINGER-VERLAG ITALIA SRL, 2018)
Weighted Morrey-type classes of functions that are harmonic in the unit disk and in the upper half plane are defined in this work. Under some conditions on the weight function, we study some properties of functions belonging to these classes. Maximum values of harmonic functions for a nontangential angle are estimated through the Hardy-Littlewood maximal function, and then the boundedness of Hardy-Littlewood operator is applied in the Morrey-type spaces. Weighted Morrey-Lebesgue type space is defined, where the shift operator is continuous with respect to shift, and its invariance with regard to the singular operator is proved. The validity of Minkowski inequality in Morrey-Lebesgue type spaces is also proved.
Keywords: Morrey-type classes; Harmonic functions; Hardy-Littlewood operator; Minkowski inequality; 30E25; 46E30; SPACES; CAMPANATO; EXPONENTS; EQUATIONS; OPERATORS; BASICITY; Mathematics